Analyzing elementary education students' understanding and needs for a digital guidebook of project-based scientific article writing - Naifah, Naifah; Batubara, Hamdan Husein; Aula, Iqbal Ahsanul; Maisaroh, Irfatin (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
This study investigates students' understanding of scientific article writing techniques, their perceptions of the challenges they face when writing these articles, and the features of guidebooks that best meet their needs. Employing a mixed-methods approach with a Convergent Parallel design, the research combines quantitative data collected through tests and questionnaires with qualitative insights from open-ended questions. The findings reveal that students' knowledge of scientific article writing falls into the moderate range (46%). While they demonstrate a good understanding of submitting articles to journals, they struggle with using AI applications, properly citing references, and documenting post-publication work. Students' primary challenges include articulating their research methodology, crafting effective sentences and paragraphs, structuring the article appropriately, utilizing AI technology during the writing process, and navigating the submission process to scientific journals. Furthermore, the study highlights students' desires for a guidebook that goes beyond theoretical discussions. They are looking for one that includes practical examples, video tutorials, project assignments, and guidance on using AI platforms to aid their writing. These insights significantly contribute to designing a scientific article writing guidebook tailored to the needs of Generation Z students, ultimately enhancing the quality of scientific writing education.